Effectiveness of a diabetes prevention program for rural women with prior gestational diabetes mellitus: study protocol of a multi-site randomized clinical trial - Jia Guo; Yujia Tang; James Wiley; Robin Whittemore; Jyu-Lin Chen (BMC, 2018)
Abstract Background In China, about 53.4 million women (11%) have type 2 diabetes (T2DM). Women with prior 2 (GDM) are at a high risk for T2DM. Postpartum lifestyle interventions have been effective in reducing T2DM for this population, but the evidence is limited to interventions provided in urban areas, despite the fact that a higher prevalence of undiagnosed T2DM was found in rural areas in China. The primary purpose of this proposed study is to examine the effect of a postpartum intensive lifestyle modification (ILSM) program on physiological health outcomes (T2DM development, insulin resistance, and weight-related variables), weight-related health behaviors (dietary intake and physical activity), and psychosocial outcomes (self-efficacy, perceived stress, social support, and health-related quality of life) compared to usual care at 3, 6, and 18 months post baseline assessment. The secondary outcomes are to identify potential mediators and moderators on change of physiological health outcomes. Methods/design A multi-site randomized clinical trial (RCT) will be conducted to examine the efficacy of an evidence-based Intensive Lifestyle Modification (ILSM) program compared with usual care for women with prior GDM living in rural areas in China. A total sample of 256 participants will be recruited in the study. The intervention consists of six bi-weekly in-person group sessions, five bi-weekly telephone consultation sessions, and three monthly telephone consultations to encourage behavior change. The usual care provided to the control group will utilize current clinical guideline and recommendations for T2DM prevention. Outcome measures include physiological variables (OGTT-2 h, HbA1c, weight, and waist circumference); weight-related health behavioral (dietary intake and physical activities); and psychosocial variables (self-efficacy and social support) at 3-, 6- and 18- month after baseline. We will also assess the potential cost-effectiveness of ILSM (net cost per T2DM case and per DALY averted) compared with usual care. Discussion If successful, this ILSM program can be adapted and used in rural areas as a blueprint for clinical guidelines to decrease T2DM by improving postpartum GDM care in China. Findings of this study are expected to make a significant contribution to public health practice and health policy related to T2DM prevention in China. Trial registration Chinese Clinical Trial Registry, ChiCTR1800015023. Registered 1 March 2018 - Retrospectively registered, http://apps.who.int/trialsearch/default.aspx.